Teachers under pressure - Galton, Maurice J.
Before writing this book, the authors asked teachers from across the world what it was like working in today's demanding classrooms. They were shocked by the answers, which painted a picture of stress and overwork, of teachers stretched to breaking-point
Includes index
Keywords: Teachers -- Job stress; Teachers -- Workload; Lehrer; Stress